Metallic Ni Promoted Mo2C-MoN Particles Supported on N-Doped Graphitic Carbon as Bifunctional Catalyst for Oxygen and Hydrogen Evolution Reaction in Alkaline Media. Issue 2 (1st January 2018) - Zhan, Yunfeng; Xie, Fangyan; Zhang, Hao; Lin, Zhipeng; Huang, Jilin; Zhang, Weihong; Sun, Xueliang; Meng, Hui; Zhang, Yueli; Chen, Jian
Abstract : A highly active and stable bifunctional electrocatalyst for oxygen evolution reaction (OER) and hydrogen evolutionreaction (HER) in alkaline media based on Ni-doped Mo2 C-MoN particles supported on porous N-doped graphitic carbon is studied in this work. The optimized Mo2 C-MoN/Ni@NC catalyst shows small over potential of 296 mV and 183 mV at 10 mA cm −2 on glassy carbon electrode for OER and HER, respectively. The best catalyst is the mixture of hexagonal Mo2 C, MoN and metallic Ni. The high catalytic performance is explained by the synergistic effect between metallic Ni and Mo compounds. The promotion effect of Ni to Mo2 C-MoN leads to high OER activity and Mo2 C is crucial for HER. The good stability and easily scale-up make the Mo2 C-MoN/Ni@NC a promising bifunctional catalyst for water splitting in alkaline media.